The teaching performance of science teachers according to artificial intelligence and its impact on the future thinking of their female students. (Journal of the College of Basic Education, 2025)
The aim of the research is to identify ( the teaching performance of science teachers according to artificial intelligence and its impact on the future thinking of their female students ) , A descriptive analytical approach was employed. The research community included 67 public girls' primary schools, encompassing 67 science teachers, 67 principals, and 7826 fifth-grade female students for the 2024-2025 academic year. The research sample consisted of 13 schools, 13 teachers, and 13 principals. The sample of female students taught by the teachers was 260 , Three tools were developed to answer research questions: the first tool (observation card) measures instructional performance using artificial intelligence (in the classroom); the second tool (questionnaire) measures instructional performance using artificial intelligence (outside the classroom); and the third tool (future thinking scale) measures the future thinking of the research sample. The research tools were validated for reliability and validity, and the psychometric properties of their items were extracted. The tools were implemented during the first semester , After applying search tools, the data was statistically processed using (split-half reliability coefficient, Kuder-Richardson Formula 20, and Cronbach's alpha) to calculate the reliability of the teaching performance of science teachers using artificial intelligence (in and outside the classroom) and the future thinking scale. The reliability coefficient for the observation sheet was 0.86, the questionnaire 0.88, and the future thinking scale 0.91. A one-sample t-test was used to extract the research variables, The results showed :Science teachers demonstrated AI-based teaching performance (both inside and outside the classroom).There is an effect of teaching performance by science teachers according to artificial intelligence on the future thinking of their students.